The Impact Of Daftar Efek Syariah (DES) Announcement To The Asii’s Abnormal Returns And Trading Volume - Utomo, Agus Saur; Jundana, Makhzumi; Prasaja, Mahendra Galih (Value : Jurnal Manajemen dan Akuntansi, 2024)
DES announcement can be an important information for investors in making investment decisions. Islamic investors have to sell their stock when their stocks are excluded from DES. On the other hand, investors who want to invest in Islamic stocks will buy stocks that are included in the DES.  The purpose of this study is to examine the impact of ASII stock reentry and exit from and into DES to the abnormal return and trading volume activity. This study uses secondary data obtained from investing.com. The data used in this study are daily stock closing prices, IHSG index and daily stock trading volume. This study follows event study methods. The first event window used in this study is 7 days before November,23,2020  and 7 days after. The second event window used is 7 days before May 24, 2023 and 7 days after. Descriptive statistic and Wilxocon sign ranks is used to analysis the data.  The results showed that there was no significant difference in abnormal returns both at the time of ASII exit and reentry. However, trading volume of ASII stock significant difference before and after exit announcement.  But when ASII stock reentry to the DES there was no significant difference.